Disruption of Orbitofronto-Striatal Functional Connectivity Underlies Maladaptive Persistent Behaviors in Alcohol-Dependent Patients - Lee, Seojung; Lee, Eun; Ku, Jeonghun; Yoon, Kang-Jun; Namkoong, Kee; Jung, Young-Chul (Psychiatry investigation, 2013)
Alcohol dependence is characterized by persistent alcohol-seeking despite negative consequences. Previous studies suggest that maladaptive persistent behaviors reflect alcohol-induced brain changes that cause alterations in the cortico-striatal-limbic circuit. Twenty one alcohol dependent patients and 24 age-matched healthy controls performed a decision-making task during functional MRI. We defined the medial orbitofrontal cortex (mOFC) as a region-of-interest and performed seed-based functional connectivity analysis. Healthy controls were more flexible in adapting an alternative behavioral strategy, which correlated with stronger mOFC-dorsal striatum functional connectivity. In contrast, alcohol dependent patients persisted to the first established behavioral strategy. The mOFC-dorsal striatum functional connectivity was impaired in the alcohol-dependent patients, but increased in correlation with the duration of abstinence. Our findings support that the disruption of the mOFC-striatal circuitry contribute to the maldaptive persistent behaviors in alcohol dependent patients.